PRODUKSI BRIKET DAN KOMPOS DARI LIMBAH CANGKANG DAN TANDAN KOSONG KELAPA SAWIT DI DESA GIRI MULYA BENGKULU UTARA - Devi Ratnawati; Morina Adfa; Eni Widiyati (Universitas Bengkulu, 2018)
The purpose of the program IbM are: (a) training waste processing of palm oil and corn as an energy (b) accompanying ways of processing and manufacturing of palm oil waste products on home industry.The implementation of the program includes improvement of knowledge and skills, demonstrations and coaching as well as technology training science applied sewage treatment production of palm oil for processing into brickets and organic fertilizers which high economic value. From some of the activities that have been done, the community was very enthusiastic in participating in these activities, especially onprocessingpalm oil empty fruit bunches and shells into briquettes and organic fertilizers.Keywords: palm oil waste, brickets, empty fruit bunches